The Role of Business Ethics in Shaping Responsible Entrepreneurship: A Systematic Literature Review - Mu'arofah, Alfiyah; Santoso, Dwi; Sari, Herla Lukmana; Sukarsih; Insani, Yogie Dana; Nasikh; Sumanto, Agus (PT Maju Malaqbi Makkarana, 2024)
This article aims to examine the role of business ethics in shaping responsible entrepreneurship through a systematic literature review. In the context of globalization and technological advancements, ethical challenges in the business world are increasingly complex. Therefore, the teaching of business ethics in entrepreneurship education is considered essential to equip aspiring entrepreneurs with knowledge and attitudes that support sustainable and responsible business practices. Through a literature analysis that includes various studies related to business ethics in entrepreneurship education categorized into 5 article categories, this article further finds that the integration of business ethics principles can increase the social and environmental awareness of entrepreneurs. In addition, the role of education in shaping responsible entrepreneurship is crucial to creating entrepreneurs who not only focus on profits but also pay attention to social and ecological impacts. These findings provide insights for the development of entrepreneurship curricula that are more based on ethics and sustainability.